Global Integration in Primary Equity Markets: The Role of U.S. Banks and U.S. Investors. (16th June 2015) - Ljungqvist, Alexander P.; Jenkinson, Tim; Wilhelm, William J.
Abstract : We examine the costs and benefits of the global integration of initial public offering (IPO) markets associated with the diffusion of U.S. underwriting methods in the 1990s. Bookbuilding is becoming increasingly popular outside the United States and typically costs twice as much as a fixed-price offer. However, on its own, bookbuilding only leads to lower underpricing when conducted by U.S. banks and/or targeted at U.S. investors. For most issuers, the gains associated with lower underpricing outweighed the additional costs associated with hiring U.S. banks or marketing in the United States. This suggests a quality/price trade-off contrasting with the findings of Chen and Ritter, particularly since non-U.S. issuers raising US20 million–US80 million also typically pay a 7% spread when U.S. banks and investors are involved.